NUBUWAT DAN OTORITAS: MENAKAR KEPEMIMPINAN KARISMATIK NABI MUHAMMAD FASE MADINAH PRA PERANG BADAR PERSPEKTIF SOSIOLOGI MAX WEBER - Moh Misbakhul Khoir (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
This article analyzes the charismatic leadership of the Prophet Muhammad during the pre-Battle of Badr period in Medina from the perspective of Max Weber’s sociology. This study employs a qualitative research method using a literature review approach, examining Islamic historical sources and Max Weber’s theory of charismatic leadership. This study found that the Prophet Muhammad emerged as a charismatic leader who gained legitimacy through his superior competence in conflict resolution, the creation of social order, and the fostering of unity in Medina. This leadership is evident in the formation of the concept of the ummah, the drafting of the Constitution of Medina as the foundation for communal life amidst diversity, and the construction of the mosque as the center of community life. According to Max Weber’s framework, the Prophet Muhammad fulfilled the characteristics of a charismatic leader. This was due to his ability to provide solutions to the social problems faced by the community and to secure the obedience of his followers based on their faith and trust in his authority. The Prophet Muhammad’s charismatic leadership has proven to have brought about tangible social change, transforming Medina from a place rife with conflict into a prosperous, peaceful, integrated, and civilized society. Keywords: The Prophet Muhammad, Charismatic Leadership, Social Change in Medina